Alveolar Ridge Dimension 6 Months After Implant Placement with Simultaneous Hard Tissue Augmentation - Heckmann, Siegfried Martin; Mörtlbauer, Barbara; Rieder, Dominik; Wichmann, Manfred; Krafft, Tim; Moralis, Antonios (International Journal of Oral & Maxillofacial Implants, 2017)
PURPOSE: When failing front teeth are replaced by implants, vestibular bone deficiencies frequently require augmentation, even though the amount of missing alveolar volume may vary. The objective of this study was to analyze the horizontal alveolar ridge dimension after implant placement and simultaneous augmentation, and to compare it to the condition at the contralateral natural site. MATERIALS AND METHODS: Forty-eight patients with a failing maxillary incisor received an immediate or early implant (Straumann Bone Level), according to a randomized study protocol. The vestibular wall of the implant site was reconstructed and moderately overcontoured with bovine hydroxyapatite and a collagen membrane (BioOss, BioGide, Geistlich). Provisional restoration followed either immediately, or after a 6-week healing period. To investigate the vestibular volume 6 months after surgery, a plaster model of the maxilla was scanned with cone beam computed tomography (CBCT; Morita 3D) and evaluated using coDiagnostiX software (Dental Wings). Statistical analysis comprised one- and two-sample t tests. RESULTS: The ridge volume was not significantly influenced by the treatment schedule. The vestibular segments had a mean ± SD volume of 207.9 ± 102.5 mm³ for the implant sites, and 202.1 ± 101.5 mm³ for the corresponding natural sites (P = .28). The difference in vestibular volume between implant sites and natural tooth sites was 10.4 ± 36.2 mm³ for immediate implantation, and 0.00 ± 31.1 mm³ for early implantation (P = .32). Comparing immediate and early restoration, a difference of 0.4 mm³ and 12.5 mm³ between the implant and contralateral site was found (P = .23). CONCLUSION: Six months after treatment, no significant differences between the alveolar volumes at augmented implant sites and natural sites were found. Moderate buccal overcontouring may have been beneficial to achieve a symmetrical contour. Long-term follow-up investigation will document if the restored volume remains stable over time.
EVALuna2:32834